Ocean Literacy in Ireland: A Review of Non-Formal Education Practices for Primary School Students - Zouboulakis, Katerina (Trinity College (Dublin, Ireland). School of Education, 2022)
The anthropogenic effects of climate change have been observed through the increase of extreme weather events and natural disasters, warming temperatures and frequent droughts, and difficulties maintaining the global food supply chain. A critical component of the Earth’s ability to modulate climate change is the expansive ocean that produces oxygen and serves as a long term carbon sink. Unfortunately, the ocean is also in jeopardy as sea temperatures and levels rise, ocean acidification and marine litter threaten habitats, and the loss of biodiversity generates instability in the marine ecosystem. Education provides a glimpse of hope, as with greater understanding of this problem, humanity can work together to provide innovative solutions while choosing to behave with sustainability in mind. Yet, global educational systems consistently omit ocean literacy from the curriculum. Ocean literacy is the understanding of the mutual reliance between the ocean and each individual. This research sought to discover the barriers to teaching ocean literacy to students, and seek the innovative approaches by exploring the non-formal learning programmes that bridge this learning gap for primary school students in Ireland. Through a targeted search of leaders in marine science and education in Ireland, four programmes were identified for analysis: Green-Schools Ireland, Explorers Education Programme, Irish Whale and Dolphin Group Floating Classroom, and Explore Your Shore. These programmes all contextualise environmental learning within the local surroundings and provide students with the conceptual and practical knowledge to engage with ocean conservation. They also highlight each individual’s ability to mitigate climate change, and enable students to conduct outreach and education events in their own communities, further spreading the concept of ocean literacy to their families and neighbours. Despite their successes, these programmes all highlight the need for partnerships with formal education institutions to reach more students and fully engage more of the Irish population. Additionally, these programmes could deeply benefit from a structured approach to evaluation that provides externally relevant metrics to demonstrate their effects on the community.
Keywords: Science Education; Education